Physiological performance of seeds and seedlings of forest species submitted to salinity by KCl (Research, Society and Development, 2021)
The objective of this research was to evaluate the physiological development of seeds and seedlings of de paricá, (Schizolobium parahyba var. amazonicum (Huber x Ducke) Barneby), paineira (Ceiba speciosa (A.St. Hil ex Brako) Ravenna) and pau de balsa (Ochroma pyramidale (Cav. ex Lam.) Urb.), submitted to different levels of salinity by potassium chloride (KCl). The experimental design adopted was entirely randomized. The evaluation of the effect of salt stress was done by moistening the seeds in aqueous solutions of KCl at concentrations: 0; 25; 50; 75; 100 mM. The following variables were evaluated: germination, first count, germination speed index, aerial part length, root length, fresh and dry mass. It was observed that the seeds of paricá and paineira had their germination, germination speed index and first count, reduced as the concentrations of KCl increased. The seedlings presented reduction in root length, fresh mass and dry of the total length in a proportional way to the increase of the dosages, demonstrating intolerance of these species to high concentrations of KCl. The seeds and seedlings of pau de balsa with exception to the variables dry mass and first count, showed tolerance to the concentrations of KCl until reaching the maximum values close to 50mM of the treatment solution.